Effects of acute cannabidiol on behavior and the endocannabinoid system in HIV-1 Tat transgenic female and male mice - Yadav-Samudrala, Barkha J.; Gorman, Benjamin L.; Barmada, Karenna M.; Ravula, Havilah P.; Huguely, Caitlin J.; Wallace, E. Diane; Peace, Michelle R.; Poklis, Justin L.; Jiang, Wei; Fitting, Sylvia (Frontiers in Neuroscience, 2024)
Background Some evidence suggests that cannabidiol (CBD) has potential to help alleviate HIV symptoms due to its antioxidant and anti-inflammatory properties. Here we examined acute CBD effects on various behaviors and the endocannabinoid system in HIV Tat transgenic mice. Methods Tat transgenic mice (female/male) were injected with CBD (3, 10, 30 mg/kg) and assessed for antinociception, activity, coordination, anxiety-like behavior, and recognition memory. Brains were taken to quantify endocannabinoids, cannabinoid receptors, and cannabinoid catabolic enzymes. Additionally, CBD and metabolite 7-hydroxy-CBD were quantified in the plasma and cortex. Results Tat decreased supraspinal-related nociception and locomotion. CBD and sex had little to no effects on any of the behavioral measures. For the endocannabinoid system male sex was associated with elevated concentration of the proinflammatory metabolite arachidonic acid in various CNS regions, including the cerebellum that also showed higher FAAH expression levels for Tat(+) males. GPR55 expression levels in the striatum and cerebellum were higher for females compared to males. CBD metabolism was altered by sex and Tat expression. Conclusion Findings indicate that acute CBD effects are not altered by HIV Tat, and acute CBD has no to minimal effects on behavior and the endocannabinoid system.